Increasing prolificacy of the fat tail Awassi sheep using the Booroola FecB gene. - Gootwine E. (Strategies for sheep and goat breeding, 1995)
The Awassi is the main type of sheep in the Middle East, where it is kept under a wide range of production systems. The prolificacy of the Awassi is low -about 1.2 lambs born per ewe lambing (LB/EL). To increase prolificacy without adverting the Awassi phenotype and adaptability, a scheme was initiated in 1986 to introduce the FecB (Booroola) gene into the Awassi. Results so far show that lamb production in Booroola Awassi crosses carrying one copy of the B allele is about 2.0 LB/EL and that milk production is not affected by the Booroola gene. Distribution of BB or B+ Awassi rams in Awassi flocks can dramatically increase their productivity. DNA markers linked to the Booroola gene can be used in selection of lambs carrying the gene.
Meeting of the joint FAO/CIHEAM Network on Sheep and Goats, Subnetwork on Animal Resources, 1995/03/26-28, Sidi-Thabet (Tunisia)